Pegylation, a Successful Strategy to Address the Storage and Instability Problems of Blood Products: Review 2011-2021 - Mehrizi, Tahereh Z.; Mirzaei, Mehdi; Ardestani, Mehdi Shafiee (Current Pharmaceutical Biotechnology, 2024)
Conjugation of polyethylene glycol (PEGylation) to blood proteins and cells has emerged as a successful approach to address some of the issues attributed to the storage of blood products, including their short half-life and instability. In this regard, this review study aims to compare the influence of different PEGylation strategies on the quality of several blood products like red blood cells (RBCs), platelets, plasma proteins, i.e., albumin, coagulation factor VIII, and antibodies. The results indicated that conjugating succinimidyl carbonate methoxyPEG (SCmPEG) to platelets could improve blood transfusion safety by preventing these cells from being attached to low-load hidden bacteria in blood products. Moreover, coating of 20 kD succinimidyl valerate (SVA)-mPEG to RBCs was able to extend the half-life and stability of these cells during storage, as well as immune camouflage their surface antigens to prevent alloimmunisation. As regards albumin products, PEGylation improved the albumin stability, especially during sterilization, and there was a relationship between the molecular weight (MW) of PEG molecules and the biological half-life of the conjugate. Although coating antibodies with short-chain PEG molecules could enhance their stabilities, these modified proteins were cleared from the blood faster. Also, branched PEG molecules enhanced the retention and shielding of the fragmented and bispecific antibodies. Overall, the results of this literature review indicate that PEGylation can be considered a useful tool for enhancing the stability and storage of blood components.
Keywords: PEG molecules